Extended autoantibody panel in Turkish patients with early-stage systemic sclerosis: Coexpressions and their influences on clinical phenotypes - Temiz Karadag, Duygu; Komac, Andac; Erez, Yesim; Birlik, Ahmet Merih; Sari, Alper; Akdogan, Ali; Cefle, Ayse (Wiley, 2023)
Background/AimTo investigate the frequency and clinical relevance of an extended autoantibody profile in patients with systemic sclerosis (SSc).Materials and MethodsIn this cross-sectional study, serum from 100 consecutive patients was subjected to indirect immunofluorescence (IIF) (HEp-20-10/primate liver mosaic) and Systemic Sclerosis Profile by EUROIMMUN to evaluate anti-nuclear antibodies (ANA) and autoantibodies against 13 different autoantibodies in patients with SSc less than 3 years.ResultsNinety-three of 100 patients were positive for ANA by IIF. Fifty-three patients showed single positivity, 26 anti-topoisomerase antibodies (anti-Scl70 ab), 16 anticentromere antibodies (ACAs), six anti-RNA polymerase III antibodies (anti-RNAPIII ab), one anti-Ku antibody, one anti-PM/Scl100 antibody, two anti-PM/Scl75 antibodies, one anti-Ro52 antibody, whereas 32 patients had multiple autoantibody positivities. Among classic SSc-specific autoantibodies, anti-Scl70 and anti-RNAPIII abs showed the highest cooccurrence (n = 4). One patient was simultaneously positive for anti-RNAPIII ab and ACA, and one was positive for ACA and anti-Scl70 ab. The clinical features were not statistically different between single and multiple autoantibody-positivity for classic SSc-specific autoantibodies (ACA, anti-Scl70 ab, and anti-RNAPIII ab), except for digital ulcer in the multiantibody positive ACA group (p = .019).ConclusionBased on our results, coexpression of autoantibodies is not uncommon in SSc patients. Although autoantibodies specific to SSc in early disease show generally known clinical features, it remains to be investigated how the coexpression of autoantibodies will affect clinical presentation. The coexpression of autoantibodies is not uncommon in systemic sclerosis (SSc) patients. Although SSc-specific autoantibodies generally show known clinical features, the clinical presentation of the coexpression in specific and nonspecific autoantibody positivity continues to be necessary.image
Keywords: autoantibody; immunoblot assay; indirect immunofluorescence assay; scleroderma-specific antibodies; systemic sclerosis